2019
DOI: 10.1155/2019/3291737
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Therapeutic Efficacy of Daunorubicin and Mitoxantrone with Bavachinin, Candidone, and Tephrosin

Abstract: The capability of flavonoids in sensitizing cancer cells was demonstrated in numerous works to chemotherapy and converse multidrug resistance by modulating efflux pumps and apoptosis mechanisms. Three flavonoids, namely, bavachinin, tephrosin, and candidone, have been recently introduced to cancer treatment research presenting various activities, such as antibacterial, immunomodulatory, cell death, and anticancer. Less information exists regarding the therapeutic significance of these flavonoids in cancer trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…[15][16][17][18] It has been reported that candidone showed antitumor effect on human cholangiocarcinoma (CCA) cells and sensitized MDR cells to daunorubicin and mitoxantrone. [19][20] In the current study, Candidone was also found to inhibit both the migration and invasion abilities of HepG2 cells. Figure 2A shows that candidone at concentration 100 µM induced cell death more than 50%.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationsupporting
confidence: 52%
“…[15][16][17][18] It has been reported that candidone showed antitumor effect on human cholangiocarcinoma (CCA) cells and sensitized MDR cells to daunorubicin and mitoxantrone. [19][20] In the current study, Candidone was also found to inhibit both the migration and invasion abilities of HepG2 cells. Figure 2A shows that candidone at concentration 100 µM induced cell death more than 50%.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationsupporting
confidence: 52%
“…Moreover, dihydromyricetin, a natural flavonoid from the leaves of Vitis heyneana , reversed MRP2-induced MDR by preventing NF-κB-Nrf2 signaling in colorectal cancer HCT116/OXA and HCT8/VCR cell lines [ 114 ]. Also, bavachinin, tephrosin, and candidone sensitized MDR MCF7/MX and EPG85.257RDB cells to daunorubicin and mitoxantrone [ 115 ].…”
Section: Anti-cancer Chemotherapy Resistancementioning
confidence: 99%
“…To overcome these problems, the application of DNR in combination with other chemotherapy drugs reduces drug resistance and intensifies the toxicity of the combined drugs on cancer cells compared to DNR alone. 12 DNR anticancer function is the result of its incorporation into the minor groove of DNA, resulting in an arrest in replication. 10 In addition, DNR inhibits the topoisomerase II enzyme by stabilizing the interaction of the enzyme and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, recent studies have reported the therapeutic effect of DNR in combination with other agents. 12 …”
Section: Introductionmentioning
confidence: 99%